Fibroblast Inward-Rectifier Potassium Current Upregulation in Profibrillatory Atrial Remodeling. Issue 5 (27th February 2015) - Qi, Xiao-Yan; Huang, Hai; Ordog, Balazs; Luo, Xiaobin; Naud, Patrice; Sun, Yiguo; Wu, Chia-Tung; Dawson, Kristin; Tadevosyan, Artavazd; Chen, Yu; Harada, Masahide; Dobrev, Dobromir; et al.
<x xml:space="preserve">Abstract</x> Rationale: Fibroblasts are involved in cardiac arrhythmogenesis and contribute to the atrial fibrillation substrate in congestive heart failure (CHF) by generating tissue fibrosis. Fibroblasts display robust ion currents, but their functional importance is poorly understood. Objective: To characterize atrial fibroblast inward-rectifier K+ current (IK1) remodeling in CHF and its effects on fibroblast properties. Methods and Results: Freshly isolated left atrial fibroblasts were obtained from controls and dogs with CHF (ventricular tachypacing). Patch clamp was used to record resting membrane potential (RMP) and IK1. RMP was significantly increased by CHF (from −43.2±0.8 mV, control, to −55.5±0.9 mV). CHF upregulated IK1 (eg, at −90 mV from −1.1±0.2 to −2.7±0.5 pA/pF) and increased the expression of KCNJ2 mRNA (by 52%) and protein (by 80%). Ba2+ (300 μmol/L) decreased the RMP and suppressed the RMP difference between controls and dogs with CHF. Store-operated Ca2+ entry (Fura-2-acetoxymethyl ester) and fibroblast proliferation (flow cytometry) were enhanced by CHF. Lentivirus-mediated overexpression of KCNJ2 enhanced IK1 and hyperpolarized fibroblasts. Functional KCNJ2 suppression by lentivirus-mediated expression of a dominant negative KCNJ2 construct suppressed IK1 and depolarized RMP. Overexpression of KCNJ2 increased Ca2+ entry and fibroblast proliferation, whereas the dominant negative KCNJ2 construct had opposite effects. Fibroblast hyperpolarization to mimic CHF effects on RMP enhanced the Ca2+ entry. MicroRNA-26a, which targets KCNJ2, was downregulated in CHF fibroblasts. Knockdown of endogenous microRNA-26 to mimic CHF effects unregulated IK1. Conclusions: CHF upregulates fibroblast KCNJ2 expression and currents, thereby hyperpolarizing RMP, increasing Ca2+ entry, and enhancing atrial fibroblast proliferation. These effects are likely mediated by microRNA-26a downregulation. Remodeling-induced fibroblast KCNJ2 expression changes may play a role in atrial fibrillation promoting fibroblast remodeling and structural/arrhythmic consequences.